The binary lottery procedure does not induce risk neutrality in the Holt & Laury and Eckel & Grossman tasks - Kirchkamp, Oliver; Oechssler, Joerg; Sofianos, Andis (Journal of economic behavior & organization, 2021)
We test whether the binary lottery procedure makes participants behave as if they are risk neutral in the Holt and Laury (2002) and Eckel and Grossman (2002) tasks. Depending on the task, we find that less than half of the participants behave as if risk neutral. In fact, when we compare the distribution of choices, we find no significant difference to standard experiments that did not use the binary lottery procedure. Using a structural model we find modest evidence that the binary lottery procedure might move participants at least slightly towards risk neutrality.